Accelerated infusion rates of rituximab are well tolerated and safe in rheumatology practice: a single-centre experience - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (SPRINGER LONDON LTD, 2013)
Due to the possible risk of infusion reactions of rituximab (RTX), a slow infusion rate (total infusion time, 255 min) is suggested for rheumatological use. However, especially in oncology field, accelerated infusion of RTX is reported to be well tolerated and safe. The aim of our study was to evaluate whether accelerated infusion rates of RTX would similarly be safe and tolerable in rheumatoid arthritis (RA) patients and other off-label rheumatological indications. All patients treated with RTX for RA and other autoimmune diseases between May 2011 and January 2012 were recruited to the study. Each treatment course consisted of two RTX 1,000 mg infusions, 2 weeks apart. Total time of the infusion for the first cycle was 255 min. Second and subsequent infusions were administered over 120 min as follows: 0-30 min, 100 mg; 30-60 min, 200 mg; 60-90 min, 300 mg; and 90-120 min, 400 mg. The Clinical Trials Classification of Adverse Events (CTCAE) version 4.3 was used to categorise side effects. The study population comprised 68 patients [F/M, 59:9; mean age, 52.4 (10.6) years]: 60 with RA, 4 with systemic lupus erythematosus (SLE), 1 with non-Hodgkin's lymphoma with SLE and 3 with vasculitis. A total of 77 fast infusions were administered. Eleven patients (16.2 %) had taken a fast infusion at the first course. A total of nine patients experienced at least one AE. Seven patients had a reaction on the first infusion (infusion-related reaction (IRR)), two patients on the second infusion and one patient on both infusions. When graded from 1 to 5 according to CTCAE v. 4.3, grade 1 IRRs were observed in a total of seven patients and grade 2 IRR in three patients. In this study of fast infusions, adverse events after RTX were mostly mild and seem to be well tolerated. Faster rituximab infusion times seem to be safe and might be incorporated into routine practice.
Keywords: Fast infusion; Rheumatoid arthritis; Rituximab; RAPID-INFUSION; CONTAINING CHEMOTHERAPY; MONOCLONAL-ANTIBODY; NECROSIS-FACTOR; ARTHRITIS; METHOTREXATE; LYMPHOMA; THERAPY; TRIAL